MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA BUKU CERITA BERGAMBAR PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Marniati Marniati; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the beginning of improved reading skills in children aged 5-6 years through media activities of picture books in TK Pertiwi namesake grandmother Tapung District of Kampar regency. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 13 children in TK Pertiwi namesake grandmother , The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. Ha sil research shows that the media picture books can improve Early reading ability in children aged 5-6 year. It Dapa t be seen from the increase in the average percentage of children reading at the beginning of the first cycle of 41.79% which is the criteria began to develop and an increase of 57.69% in the second cycle be 65.90% which are in developing criteria according to expectations. So, the media picture books can improve Early reading ability 5-6 years old children in kindergarten Pertiwi namesake grandmother Tapung District of Kampar regency.Keywords : Literacy Starters, Media Picture Story Books